Malignant Lymphomas : Biology and Molecular Pathogenesis - Bergsagel, Leif; Castillo, Jorge J.; Cesarman, Ethel; Chan, Wing C.; Chesi, Marta; Cortés, José Rodríguez; Crowe, Jennifer L.; Dai, Beiying; Dalla-Favera, Riccardo; Dominguez-Sola, David; Du, Ming-Qing; Falini, Brunangelo; et al. (De Gruyter, 2016)
This book is an up to date compendium on the biology and molecular pathogenesis of lymphomas, which represent malignant cancers of the lymphoid system. With its focus on the biology and genetic basis of these diseases, the book is of interest to basic scientists, biologists, clinical hematologists and pathologists as well as medical students. Different chapters will cover all major lymphoma subtypes, as well as chronic lymphocytic leukemia and selected less common lymphoma entities such as T-cell lymphomas and central nervous system lymphomas.